Childhood atopic dermatitis: A cross-sectional study of relationships between child and parent factors, atopic dermatitis management, and disease severity. Issue 1 (January 2015) - Mitchell, Amy E.; Fraser, Jennifer A.; Ramsbotham, Joanne; Morawska, Alina; Yates, Patsy
Abstract Background Successful management of atopic dermatitis poses a significant and ongoing challenge to parents of affected children. Despite frequent reports of child behaviour problems and parenting difficulties, there is a paucity of literature examining relationships between child behaviour and parents' confidence and competence with treatment. Objectives To examine relationships between child, parent, and family variables, parents' self-efficacy for managing atopic dermatitis, self-reported performance of management tasks, observed competence with providing treatment, and atopic dermatitis severity. Design Cross-sectional study design. Participants A sample of 64 parent-child dyads was recruited from the dermatology clinic of a paediatric tertiary referral hospital in Brisbane, Australia. Methods Parents completed self-report questionnaires examining child behaviour, parents' adjustment, parenting conflict, parents' relationship satisfaction, and parents' self-efficacy and self-reported performance of key management tasks. Severity of atopic dermatitis was assessed using the Scoring Atopic Dermatitis index. A routine home treatment session was observed, and parents' competence in carrying out the child's treatment assessed. Results Pearson's and Spearman's correlations identified significant relationships (p < .05) between parents' self-efficacy and disease severity, child behaviour difficulties, parent depression and stress, parenting conflict, and relationship satisfaction. There were also significant relationships between each of these variables and parents' self-reported performance of management tasks. More profound child behaviour difficulties were associated with more severe atopic dermatitis and greater parent stress. Using multiple linear regressions, significant proportions of variation in parents' self-efficacy and self-reported task performance were explained by child behaviour difficulties and parents' formal education. Self-efficacy emerged as a likely mediator for relationships between both child behaviour and parents' education, and self-reported task performance. Direct observation of treatment sessions revealed strong relationships between parents' treatment competence and parents' self-efficacy, outcome expectations, and self-reported task performance. Less competent task performance was also associated with greater parent-reported child behaviour difficulties, parent depression and stress, parenting conflict, and relationship dissatisfaction. Conclusion This study revealed the importance of child behaviour to parents' confidence and practices in the context of atopic dermatitis management. Children with more severe atopic dermatitis are at risk of presenting with challenging behaviour problems and their parents struggle to manage the condition successfully.